A novel risk‐scoring system for predicting lymph node metastasis of rectal neuroendocrine tumors. Issue 5 (10th June 2020) - Chida, Keigo; Watanabe, Jun; Hirasawa, Kingo; Inayama, Yoshiaki; Misumi, Toshihiro; Kunisaki, Chikara; Endo, Itaru
Abstract: Aim: Although rectal neuroendocrine tumors (NETs) are considered to be rare low‐grade malignancies when lymph node metastasis (LNM) is present, their degree of malignancy is comparable to that of colorectal cancer (CRC). However, it remains unclear as to which patients require radical lymph node dissection. The aim of this study was to elucidate the risk factors for LNM and develop a risk‐scoring system for LNM to help determine appropriate therapeutic approaches. Methods: In this study, we examined 103 patients with rectal NETs who underwent local resection (n = 55) or radical resection with LN dissection (n = 48). We evaluated each pathological feature, including the depth of submucosal invasion (SM depth) and tumor budding grade. Results: According to our univariate analyses and previous reports, the significant five risk factors for LNM were weighted with point values: 2 points for tumor size ≥ 15 mm and muscularis invasion, and 1 point each for SM depth ≥ 2000 µm, positive lymphovascular invasion, budding grade 3, and vertical margin. The area under the receiver operating curve for the scoring system was 0.899 (95% CI: 0.843‐0.955). When a score of 2 was used as the cut‐off value, the sensitivity and specificity for the prediction of LNM were 100% and 72.1%, respectively. Conclusions: The risk‐scoring system for LNM of rectal NETs showed high diagnostic performance. Using this risk‐scoring system, it is possible to predict the risk of LNM and thereby potentially avoid unnecessary surgery. Further prospective external validation studies should be performed. The study was registered in the Japanese Clinical Trials Registry as UMIN000036658. Abstract : The risk‐scoring system for LNM of rectal NETs could predict the risk of LNM and thereby potentially avoid unnecessary surgery.